2014
DOI: 10.1136/bcr-2013-201827
|View full text |Cite
|
Sign up to set email alerts
|

Carney complex: fourth time excision of recurrent atrial myxoma via left thoracotomy

Abstract: SUMMARYWe report a case of a 51-year-old male patient with a known history of Carney complex, who was operated on for the fourth time due to recurrent left atrial myxomas. Despite surgical challenge, the operation was uneventful.The patient had a difficult postoperative period and needed further treatment for complications. After a prolonged recovery, he is currently well and remains myxoma-free up until now (36 months postsurgery) with regular follow-up using cardiac CT and transthoracic echocardiogram. BACKG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…11 Patients should have an echocardiogram, or alternatively a cardiac CTscan or cardiac MRI, performed 6 months after their surgery for outpatient follow-up. 5 In our case, we utilized and advise multimodality cardiac imaging for presurgical planning and intraoperative TEE to guide surgical management. The cardiac CT scan in the preoperative period helped identify the left atrial myxomas that were not reported on the echocardiogram and cardiac MRI that were performed outside of our institution prior to our presurgical evaluation of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…11 Patients should have an echocardiogram, or alternatively a cardiac CTscan or cardiac MRI, performed 6 months after their surgery for outpatient follow-up. 5 In our case, we utilized and advise multimodality cardiac imaging for presurgical planning and intraoperative TEE to guide surgical management. The cardiac CT scan in the preoperative period helped identify the left atrial myxomas that were not reported on the echocardiogram and cardiac MRI that were performed outside of our institution prior to our presurgical evaluation of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In isolated cardiac myxomas, surgical treatment is typically curative. However, patients with CNC showed higher recurrence rates (10‐21% vs 4‐7% for isolated myxomas) . Reasons for relapses include inadequate resections, intraoperative implantation of parts of the tumor, and multi‐centric tumor location .…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with CNC showed higher recurrence rates (10-21% vs 4-7% for isolated myxomas). [30][31][32][33][34][35][36][37][38] Reasons for relapses include inadequate resections, intraoperative implantation of parts of the tumor, and multi-centric tumor location. 29,30,37 In our study, the rate of multiple cardiac myxomas in CNC was significantly higher than that of isolated cardiac myxomas (30% vs 11.17%, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…showed a patient with Carney complex who had four recurrent of CM, all in the LA. The patient underwent excision four times and was tumor-free at 36-month follow-up [ 38 ].…”
Section: Discussionmentioning
confidence: 99%